A study to assess inhaler technique and its potential impact on asthma control in patients attending an asthma clinic. (May 2014) - Harnett, C. M.; Hunt, E. B.; Bowen, B. R.; O'Connell, O. J.; Edgeworth, D. M.; Mitchell, P.; Eustace, J. A.; Henry, M. T.; Kennedy, M. P.; Plant, B. J.; Murphy, D. M.
Abstract Objectives: The aim of this study was to evaluate inhaler technique and symptom control in patients with poorly controlled asthma at baseline and at follow-up in a dedicated asthma clinic in a tertiary hospital. We also investigated the impact of asthma on these patients' quality of life. Methods: Patients referred to a newly established asthma clinic in Cork University Hospital were prospectively recruited over a 6-month period. Their inhaler technique was assessed by a pulmonary nurse specialist using a validated scoring system. They received instruction on inhaler usage when scores were suboptimal. Patients completed a validated asthma control questionnaire (ACQ) and asthma quality of life questionnaire (AQLQ). At follow-up 3–4 months later, the inhaler technique was reassessed and the ACQ questionnaire repeated. Results: Forty-six patients were recruited (female = 74%), and 40/46 were followed up. Mean [SD] FEV1 % predicted at baseline = 76.5% [21.5]. About 63% of the patients were classified as incorrectly using their inhaler at their initial assessment. This decreased to 20% at follow-up, indicating an overall significant improvement in inhaler usage post-training (p = 0.003). ACQ scores improved significantly from median [interquartile range] 2.70 [1.66] to 2.00 [1.90] (p = 0.002). Baseline measurement indicated that patients' quality of life was moderately affected by asthma, with a median AQLQ score of 4.75 [1.97]. Conclusion: This study demonstrates the importance of educating and formally assessing inhaler technique in patients with asthma as a part of their ongoing clinical review.